Preparation and Evaluation of Extended Release Pellets of Chiral Molecules of s-Metoprolol Succinate by Different Technology (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: The present research was focus on preparation and evaluation of extended pellets of chiral molecule of metoprolol succinate, i.e., s-metoprolol succinate. Materials and Methods: For preparation of extended release (ER), drug pellets of s-metoprolol succinate were prepared using two different technology, i.e., extrusion and spheronization and drug layering utilizing Wurster technology. These drug-loaded pellets were further coated with ethyl cellulose as rate controlling polymer, hypromellose as pore former, acetyl tributyl citrate as plasticizer, and talc as anti-adhering agent by fluid bed process to yield ER coated pellets. Results and Discussion: ER coating was optimized using center composite design for both drug layered pellets. Higher percentage of ER coating required to control the drug release from pellets prepared by extrusion and spheronization compared to pellets prepared by fluid bed technology. These are due to the wider particle size distribution of the pellets prepared by extrusion and spheronization. Drug release of pellets was comparable to that of reference product. Conclusion: ER coated pellets of chiral molecules of metoprolol succinate were successfully prepared by extrusion and spheronization technique and using fluid bed technology. Percentage ER coating required to control the drug release is less in pellets prepared by fluid bed technology compared to ER coated pellets prepared by extrusion and spheronization technique. This may be due to narrower particle size distribution and more sphericity of the pellets prepared by the fluid bed technology.